The Effect of Soy Bean (Glycine max) to mice (Mus musculus) Renal Cellâs Histophatology Induced with Reused Palm Oil - prabowo, miftah nurizzahid; Listyaningsih, Endang; Afifah, Zulaika Nur (Nexus Biomedika, 2015)
Background: The reused palm oil is usually used by people to cook especially for cooking food. In the society the palm oil is usually used by deep frying method.Â This methode usually destroys the chemical chain in the palm oil.As results from this deep frying methode many toxic and free radical are formed, this can be dangerous for human body. Soy bean (Glycine max) one of food that contains fitoestrogen and the descents isoflavon. The isoflavone will protect human body from free radicals and has antiinflammatory actitivity. Method: This study was an experimental laboratory using the posttest only controlled group design. The sample used 27 mice, 8-10 weeks old and weights Â± 20 g. Samples were divided into 4 groups. Group of KKand KP1, in order, was only given distilled water and 0.06 ml of reused palm oil in addition to distilled waterfor 14 days. whilegroup of KP2 and KP3 was respectively given soy bean powder at a dose of 5.6 mg and 11.2 mg per 20 g of body weight each of mice alongside with 0.06 ml of reused palm oil and distilled water for 14 days. On 15th day, samples were sacrificed to be made preparations of left and right kidney by methode of parafin block and HE staining. The number of tubule proximal cell was calculated based on quantifying of pyknosis, karyorrhexis, and karyolysis. Data were analyzed using the Kruskal Walis test (Î± = 0.05) and continued with Mann-Whitney test (Î± = 0.05). Result: : The Kruskal Wallis test showed that there was significant difference between the four groups. Mann-Whitney test showed there was significant difference between groups of KK-KP1, KK-KP2, KK-KP3, KP1-KP2, KP1-KP3, and KP2-KP3. Conclusion: Soy bean (Glycine max.) can prevent the renal cell damage of mice which are induced by reused palm oil and the increase of soy bean dosage can increase protection effect to renal cell damage of mice which are induced by reused palm oil. Keywords: soy bean, reused palm oil, the renal cell damage